Pediatric Provider Experiences with Implementation of Routine Mental Health Screening. Issue 1 (January 2021) - Godoy, Leandra; Gordon, Sara; Druskin, Lindsay; Long, Melissa; Kelly, Katherine Patterson; Beers, Lee
ABSTRACT: Objective: Despite the utility of universal screening, most pediatric providers rarely use mental health (MH) screening tools. As such, provider descriptions of their experiences with universal screening are limited. The goal of this study was to describe barriers to, and facilitators of, universal MH screening implementation, the perceived impact of such screening, impressions of a screening-focused quality improvement (QI) Learning Collaborative, and lessons learned. Method: We invited primary care clinicians participating in a large-scale QI Learning Collaborative on MH screening (n = 107) to complete postproject interviews. Interviews were transcribed and analyzed using constant comparative qualitative analysis, an inductive, iterative process. Results: Eleven interviews were completed and analyzed. Practice sites included academic health centers, a private practice, and a federally qualified health center. Providers described the positive impact of screening (increased identification of MH concerns) and barriers and facilitators of screening at the practice level (clinic and leadership buy-in and electronic medical record integration), the provider level (provider beliefs about the importance of screening), and the patient level (parent literacy). Challenges of linking families with care after screening included lack of adequate referrals, long wait lists, limited bilingual providers, insurance gaps, and inadequate feedback loops. Access to on-site MH clinicians and participation in the Learning Collaborative were described as beneficial. Conclusion: Findings elucidate how universal MH screening can be sustainably integrated into real-world primary care settings and may facilitate the uptake of American Academy of Pediatrics recommendations for best practices in screening for MH concerns. Abstract : This article has supplementary material on the web site: www.jdbp.org.